Realism and Naturalism in Samrat Upadhyay’s The Guru of Love - Bimal Kishore Shrivastwa (Journal of Language and Literature, 2021)
This research project seeks to explore realism and naturalism in Samrat Upadhyay's novel, The Guru of Love, in the context of Nepalese society. It analyses how the novel delineates a realistic account of Nepalese middle-class people's hardships, struggles, and problems they face internally and externally through the character of Ramchandra, the protagonist of the fiction, an ordinary mathematics teacher who faces some hindrances in search of a better life and developing a career in the capital city. The principal objective of the study is to find the realistic, naturalistic, and materialistic elements in the novel, to examine the psychic predispositions that characters come through realistically, and to analyze the role of love and sex in terms of spirituality and emancipation as they all fall into the parameters of naturalism and realism. This study is developed through a theoretical framework based on realism and naturalism for the close textual analysis of the novel. The principal finding of the research paper is that the major characters of the novel, The Guru of Love, suffer from the conflict between their desires and their socio-economic realities. The article also surveys how material prosperity fails to resolve all the problems that human being goes through. It is expected that the paper stands as a reference for the research scholars interested to explore in the area.